Consumption and Literature - Lawlor, C. author. aut Link
VIII, 243 p.
Keywords: This book seeks to explain how consumption - a horrible disease - came to be the glamorous and artistic Romantic malady. It tries to explain the disparity between literary myth and bodily reality, by examining literature and medicine from the Renaissance to the late Victorian period, covering a wide range of authors and characters.